2013
DOI: 10.1002/ams2.6
|View full text |Cite|
|
Sign up to set email alerts
|

Role of endogenous IL‐18 in the lung during endotoxin‐induced systemic inflammation

Abstract: Background: Overactivated neutrophils are causes of acute lung injury, which is a major clinical problem with significant morbidity and mortality in sepsis. Serum interleukin (IL)-18 levels correspond to severity of systemic inflammation.Aim: To elucidate the roles of endogenous IL-18 in lung injury during endotoxin-induced systemic inflammation. Methods: Wild-type (WT) and IL-18 gene knockout (KO) mice were injected with lipopolysaccharide (40 mg/kg) intraperitoneally and killed. Lungs were collected at 0 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 23 publications
2
1
0
Order By: Relevance
“…Our previous study suggested that endogenous IL-18 promoted lung edema and contributed to poor outcomes during endotoxemia [27]. The present study showed that in the absence of IL-18 (IL-18 KO) lung and liver injury were less severe and a survival was better after LPS injection compared with WT mice.…”
Section: Discussionsupporting
confidence: 48%
“…Our previous study suggested that endogenous IL-18 promoted lung edema and contributed to poor outcomes during endotoxemia [27]. The present study showed that in the absence of IL-18 (IL-18 KO) lung and liver injury were less severe and a survival was better after LPS injection compared with WT mice.…”
Section: Discussionsupporting
confidence: 48%
“…The results obtained in this study were completely consistent with those obtained in similar experimental studies [16,17]. It was shown that intratracheal administration of LPS (5 mg/kg) to rats after 24 h led to the accumulation of large numbers of neutrophils in the intra-and interalveolar space, thickening of the alveolar wall due to edema, increased of myeloperoxidase activity, lipid peroxidation and caspase-3 activity [16].…”
Section: Fig 4 Microphotographs Of the Lung Tissue Of Rats With An Ex...supporting
confidence: 91%
“…12 hours after intraperitoneal administration of LPS (40 mg/kg) in the blood of wild-type mice significantly increased levels of interleukin-18, in the lungs appeared pronounced neutrophilic infiltration and increased activity of myeloperoxidase and caspase-3 on the background of significant interalveolar edema, increased apoptosis [17]. According to the authors, endogenous interleukin-18, formed by LPS, induces the expression of intercellular adhesion mole cules (ICAM-1), which recruits neutrophils and inhibits their apoptosis with increased oxidative damage to lung tissue, leading to edema.…”
Section: Fig 4 Microphotographs Of the Lung Tissue Of Rats With An Ex...mentioning
confidence: 99%